Paul Wysocki, Wiggsy Sivertsen and Ken Yeager. - Sahl, Ted (photographer):::Creator::::::::::::
Campaigning to defeat California Proposition 64 are (left to right) Paul Wysocki, Wiggsy Sivertsen, and Ken Yeager.